2018
DOI: 10.1177/1367493518777311
|View full text |Cite
|
Sign up to set email alerts
|

Leaders’ limitations and approaches to creating conditions for interaction and communication in parental groups: A qualitative study

Abstract: The aim of this study was to describe and understand parental group (PG) leaders' experiences of creating conditions for interaction and communication. The data consisted of 10 interviews with 14 leaders. The transcribed interviews were analysed using thematic analysis. The results showed that the leaders' ambition was to create a parent-centred learning environment by establishing conditions for interaction and communication between the parents in the PGs. However, the leaders' experience was that their profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A possible explanation for this challenge may be found in an unawareness of one's leadership role. There is a lack of formal group leadership education in Bachelor/Master Education of Science in Nursing (Forslund Frykedal et al, 2019;Lefèvre et al, 2015) and instead the leaders need to develop their group leadership role at their workplace. Herbig and Bussing (2004) argued that knowledge acquired and developed implicitly in the workplace seems to be difficult to verbalize explicitly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for this challenge may be found in an unawareness of one's leadership role. There is a lack of formal group leadership education in Bachelor/Master Education of Science in Nursing (Forslund Frykedal et al, 2019;Lefèvre et al, 2015) and instead the leaders need to develop their group leadership role at their workplace. Herbig and Bussing (2004) argued that knowledge acquired and developed implicitly in the workplace seems to be difficult to verbalize explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of health professionals' views regarding parental groups have shown that they strongly believe in these groups as a support method (Lefèvre et al, 2015). There is an ambition to create parent-centered learning environments by establishing the conditions for interaction and communication between the parents (Forslund Frykedal, Rosander, Barimani, & Berlin, 2019). However, previous studies have shown that leaders often feel that they lack the pedagogical skills to be able to create well-functioning groups (Forslund Frykedal et al, 2019;Lefèvre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation